2022
DOI: 10.3138/cjhs.2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

What “Counts” as first sex between women? Results from a study of first sex among women who have sex with women

Abstract: First sex is most often defined by first penile-vaginal intercourse (PVI) among cisgender heterosexual individuals or first anal intercourse among cisgender men who have sex with men. The importance given to penetration and PVI as the markers of first sex has contributed to the invisibility of women who have sex with women’s (WSW) sexualities. Eighty-four WSW aged 16 to 25 years ( M = 21.96 years, SD = 2.44; 79% cisgender) completed an online survey wherein they categorized a series of partnered behaviours as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Germane to this, research has found that women's lower likelihood of experiencing physical pleasure and orgasm when engaging in heterosexual sex results in lower expectancies of pleasure and orgasm [27,28] and has found women to feel less entitled to their own pleasure, while prioritizing the relationship and their partner's pleasure [9,[29][30][31][32]. The prioritization of the partner's pleasure over their own may further emanate from feelings of shame and guilt and a desire to align with one's femininity and sexual identity [33], which might be threatened by female sexual dysfunction in light of societal norms of implying PVI as "having sex" [34] -leaving women feeling unable to fulfil their own and their partners' expectations when refraining from penetrative sex when experiencing pain during PVI.…”
Section: Sexual Scripts and A Restrictive Definition Of Sexmentioning
confidence: 99%
“…Germane to this, research has found that women's lower likelihood of experiencing physical pleasure and orgasm when engaging in heterosexual sex results in lower expectancies of pleasure and orgasm [27,28] and has found women to feel less entitled to their own pleasure, while prioritizing the relationship and their partner's pleasure [9,[29][30][31][32]. The prioritization of the partner's pleasure over their own may further emanate from feelings of shame and guilt and a desire to align with one's femininity and sexual identity [33], which might be threatened by female sexual dysfunction in light of societal norms of implying PVI as "having sex" [34] -leaving women feeling unable to fulfil their own and their partners' expectations when refraining from penetrative sex when experiencing pain during PVI.…”
Section: Sexual Scripts and A Restrictive Definition Of Sexmentioning
confidence: 99%
“…Bien que largement critiqué, l'impératif coïtal continue d'exercer son hégémonie dans la sphère intime hétérosexuelle (Horowitz et Bedford, 2017 ;Séguin et Blais, 2019), et les adultes hétérosexuel•les inexpérimenté•es sexuellement continuent d'y référer comme le marqueur le plus consensuel de la transition à une vie sexuelle active (Boislard, 2014). Il s'agit d'ailleurs d'un biais phallocentrique vivement critiqué dans les écrits scientifiques portant sur les diversités sexuelles (Dion et Boislard, 2022).…”
Section: Cadre Théorique L'inexpérience Sexuelle Chez Les Jeunes Adultesunclassified
“…Les résultats de l'étude, axés sur une méthode qualitative auprès d'usagers des forums et d'une analyse fine des fils de discussion, mettent en exergue la souffrance psychologique causée par la diffusion hétéronormative et phallocentrée de représentations aliénantes en ce qui concerne l'inexpérience sexuelle. Ainsi les deux autrices identifient-elles plusieurs formes d'injonctions sexuelles génératrices d'angoisse et de diffusion normative d'une certaine forme de pratiques, telles que l'impératif coïtal (Dion et Boislard, 2022) ou l'obligation sexuelle liée à l'horloge sociale (Gupta, 2015). Comme dans tout ou partie des communautés de patients ou de proches aidants, les porteurs de savoirs biomédicaux légitimés par le système de santé y sont très minoritaires (d'autant plus dans le cadre de collectifs non liés à des associations de patients très institutionnalisées, voire d'autres organisations de santé).…”
Section: Soutien Social Et Pair-aidance Numériquesunclassified